Fatores associados à diferença clinicamente significativa da qualidade de vida relacionada à saúde após condicionamento físico em pacientes com DPOC - Dourado, Victor Zuniga; Antunes, Letícia Cláudia de Oliveira [UNESP]; Tanni, Suzana Erico [UNESP]; Godoy, Irma [UNESP] (Sociedade Brasileira de Pneumologia e Tisiologia, 2009)
OBJETIVO: Investigar os fatores associados à diferença clinicamente significativa da qualidade de vida (DCSQV) após condicionamento físico em pacientes com DPOC. MÉTODOS: Trinta e cinco pacientes foram submetidos a 12 semanas de condicionamento físico, envolvendo treinamento de força e exercício aeróbio leve. Composição corporal, teste incremental e de endurance em esteira, teste de caminhada de seis minutos, força muscular periférica, PImáx, baseline dyspnea index (BDI) e Saint George's Respiratory Questionnaire (SGRQ) foram avaliados antes e após o treinamento, e suas alterações (Δ) foram calculadas. A DCSQV foi definida como a redução > 4% no escore total do SGRQ. Os pacientes que responderam ao treinamento, apresentando DCSQV, foram alocados no grupo respondedores (R; n = 24), e os demais pacientes foram alocados no grupo não-respondedores (NR; n = 11). RESULTADOS: Os seguintes resultados foram significativamente maiores no grupo R que no grupo NR (p < 0,05): VEF1 (1,48 ± 0,54 L vs. 1,04 ± 0,34 L), VEF1/CVF (47,9 ± 11,7% vs. 35,5 ± 10,7%), PaO2 (74,1 ± 9,7 mmHg vs. 65,0 ± 8,9mmHg) e ΔBDI [mediana (interquartil); 2,0 (0,0-3,5) vs. 0,0 (0,0-1,0)]. Houve correlação significativa (p < 0,01) de ΔSGRQ-sintomas (r = 0,44), ΔSGRQ-atividade (r = 0,62) e ΔSGRQ-total (r = 0,60) com ΔBDI. Após regressão logística, apenas ΔBDI foi selecionado como determinante da DCSQV. CONCLUSÕES: A DCSQV após o condicionamento físico está associada principalmente à redução da dispneia nos pacientes com DPOC. Portanto, são necessárias estratégias de tratamento visando interromper o ciclo dispneia-sedentarismo-dispneia nesses pacientes.

OBJECTIVE: To identify factors associated with the minimal clinically important difference (MCID) for health-related quality of life (HRQoL) after physical conditioning in patients with COPD. METHODS: Thirty-five patients were submitted to a 12-week program of physical conditioning (strength training plus low-intensity aerobic exercise). Body composition, incremental treadmill test results, endurance treadmill test results, six-minute walk test results, peripheral muscle strength, MIP, baseline dyspnea index (BDI) and Saint George's Respiratory Questionnaire (SGRQ) scores were assessed at baseline and after the program, thus allowing the variations (Δ) to be calculated. The MCID for HRQoL was defined as a reduction of > 4% in the SGRQ total score. Subjects who responded to the program, achieving the MCID for HRQoL, were allocated to the responders (R) group (n = 24), and the remainder were allocated to the non-responders (NR) group (n = 11). RESULTS: The values obtained for the following variables were significantly higher in group R than in group NR (p < 0.05): FEV1 (1.48 ± 0.54 L vs. 1.04 ± 0.34 L); VEF1/FVC (47.9 ± 11.7% vs. 35.5 ± 10.7%); PaO2 (74.1 ± 9.7 mmHg vs. 65.0 ± 8.9 mmHg); and ΔBDI, expressed as median and interquartile range (2.0 [0.0-3.5] vs. 0.0 [0.0-1.0]). The ΔBDI correlated significantly with the ΔSGRQ symptoms domain score, activity domain score and total score (r = 0.44, 0.60 and 0.62, respectively, p < 0.01 for all). After logistic regression, only ΔBDI remained as a predictor of MCID for HRQoL. CONCLUSIONS: Achieving the MCID for HRQoL after physical conditioning is associated with dyspnea reduction in COPD patients. Therefore, there is a need to develop treatment strategies designed to interrupt the dyspnea-inactivity-dyspnea cycle in such patients.
Factors associated with the minimal clinically important difference for health-related quality of life after physical conditioning in patients with COPD
Keywords: Doença pulmonar obstrutiva crônica; Qualidade de vida; Dispneia; Exercício; Reabilitação; Pulmonary disease, chronic obstructive; Quality of life; Dyspnea; Exercise; Rehabilitation